#### Answer

$q-5t^{2}$

#### Work Step by Step

$d=a_{n+1}-a_{n}=\left( -9t^{2}+3q\right) -\left( -4t^{2}+2q\right) =\left( -4t^{2}+2q\right) -\left( t^{2}+q\right) =q-5t^{2}$

Published by
Pearson

ISBN 10:
013421742X

ISBN 13:
978-0-13421-742-0

$q-5t^{2}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.